The chemicals between us: first results of the cluster analyses on anatomy embalming procedures in the German-speaking countries - Kerner, Alexander; Biedermann, Uta; Bräuer, Lars; Caspers, Svenja; Doll, Sara (Anatomical sciences education, 2023)
Hands-on courses utilizing preserved human tissues for educational training offer an important pathway to acquire basic anatomical knowledge. Owing to the reevaluation of formaldehyde limits by the European Commission, a joint approach was chosen by the German-speaking anatomies in Europe (Germany, Austria, Switzerland) to find commonalities among embalming protocols and infrastructure. A survey comprising 537 items was circulated to all anatomies in German-speaking Europe. Clusters were established for "ethanol"-, formaldehyde-based ("FA"), and "other" embalming procedures, depending on the chemicals considered the most relevant for each protocol. The logistical framework, volumes of chemicals, and infrastructure were found to be highly diverse between the groups and protocols. Formaldehyde quantities deployed per annum were three-fold higher in the "FA" (223 L/a) compared to the "ethanol" (71.0 L/a) group, but not for "other" (97.8 L/a), though the volumes injected per body were similar. "FA" was strongly related to table-borne air ventilation and total fixative volumes ≤1000 L. "Ethanol" was strongly related to total fixative volumes >1000 L, ceiling- and floor-borne air ventilation, and explosion-proof facilities. Air ventilation was found to be installed symmetrically in the mortuary and dissection facilities. Certain predictors exist for the interplay between the embalming used in a given infrastructure and technical measures. The here-established cluster analysis may serve as decision supportive tool when considering altering embalming protocols or establishing joint protocols between institutions, following a best practice approach to cater toward best-suited tissue characteristics for educational purposes, while simultaneously addressing future demands on exposure limits.
First published: 15 May 2023
Gesehen am 14.12.2023